Concurrent open-pit mine production and in-pit crushing–conveying system planning. Issue 10 (2nd October 2020) - Paricheh, Morteza; Osanloo, Morteza
Abstract : Optimally planned In-Pit Crushing and Conveying (IPCC) systems could resolve the transportation challenges of open-pit mining operations. There is a direct correlation between IPCC planning, Open-Pit Mine Production Scheduling (OPMPS) and the haul fleet sizing problems. Solving each said problem individually does not result in global optimum, nor does it produce a practical solution. This paper develops a new mix-integer linear programming model (called M1) to integrate these problems. The model was validated by comparing it against two other benchmark models where both omit the IPCC planning. The second model (M2) combines OPMPS and truck fleet sizing, but the third one (M3) is a conventional model that deals with OPMPS and fleet sizing, separately. The results indicated that the proposed model outperforms the conventional OPMPS by adding the in-pit crushing values to the project and improving the NPVs by 3.3 and 2.4% for the hypothetical examples.